2017
DOI: 10.1039/c6gc03465a
|View full text |Cite
|
Sign up to set email alerts
|

A copper-catalyzed oxidative coupling reaction of arylboronic acids, amines and carbon dioxide using molecular oxygen as the oxidant

Abstract: A Cu-catalyzed oxidative coupling reaction of arylboronic acids, amines and carbon dioxide is described, providing a route to O-aryl carbamates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…In this particular system, CO2 works as a co-catalyst in association with the ruthenium complex, generating a carbamate as a reaction intermediate (Scheme 37) [270]. In addition to the above mentioned reactions, Jiang et al reported the involvement of Cu(II) and Cu(III) carbamates in the oxidative coupling of arylboronic acids [322] and in the cyclization of enynes [323] from amines and CO2. In order to support the hypothesis of an in situ formed Cu(II) carbamate, the catalytic activity of [Cu(O2CNBn)2(NHBn2)2] was evaluated, providing moderate to good results in term of product yields.…”
Section: Co 2 Activation Routesmentioning
confidence: 99%
“…In this particular system, CO2 works as a co-catalyst in association with the ruthenium complex, generating a carbamate as a reaction intermediate (Scheme 37) [270]. In addition to the above mentioned reactions, Jiang et al reported the involvement of Cu(II) and Cu(III) carbamates in the oxidative coupling of arylboronic acids [322] and in the cyclization of enynes [323] from amines and CO2. In order to support the hypothesis of an in situ formed Cu(II) carbamate, the catalytic activity of [Cu(O2CNBn)2(NHBn2)2] was evaluated, providing moderate to good results in term of product yields.…”
Section: Co 2 Activation Routesmentioning
confidence: 99%
“…In 2017, Jiang’s group developed a novel copper-promoted oxidative coupling reaction of arylboronic acids, amines and CO 2 (Scheme ). In this example, the initially added Cu 2 O can be oxidized into Cu­(II) complex A in the presence of O 2 , amine, and CO 2 . After that, A undergoes coordination exchange with pyridine facilitated by BF 3 ·Et 2 O, generating intermediate B .…”
Section: Miscellaneous C–cu Bond Formation For Co2 Conversionmentioning
confidence: 99%
“…In 2017, Jiang's group developed a novel copper-promoted oxidative coupling reaction of arylboronic acids, amines and CO 2 (Scheme 33). 81…”
Section: ■ C−cu Bond Formation By Transmetalationmentioning
confidence: 99%
“…Additionally, a more convenient route to O -aryl carbamates by a copper(I)-catalyzed oxidative coupling reaction between arylboronic acids, amines and CO 2 was developed (Scheme 18b) [103]. At the same time, BF 3 ·OEt 2 was employed as the promoter and O 2 as the oxidant.…”
Section: Chemical Fixation Of Co2 Through C-n Bond Formationmentioning
confidence: 99%